SVILUPPO DI NUOVE STRATEGIE ANTIVIRALI DIRETTE CONTRO L' RNA POLIMERASI DEL VIRUS DELL'INFLUENZA - Muratore, Giulia (Università degli studi di Padova, 2011)
Influenza (flu) is an airborne highly-infectious disease, characterized by high morbidity and significant mortality, especially in at-risk population (young children, elderly people, patients with cronical disease). Annually, 20% of general population is affected by seasonal epidemics sustained by genetic variants of already circulating influenza virus strains. For this reason the vaccine has to be changed every year with a considerable economic impact. Furthermore, the influenza virus is responsible for occasional pandemics affecting million of people worldwide. The migratory water bird are the natural reservoir for the avian flu. The recent avian flu virus that affected humans suggests that a new flu epidemic could be able to overcome the species barrier and spread from human to human. For these reasons there is an urgent need to develop a new drug able to target a conservative flu motif. To date, there are a few commercially available drugs that target some envelope viral proteins: neuraminidase (NA) and the M2 ion channel. Oseltamivir (Tamiflu) and zanamivir are NA inhibitors, which prevent the release of the viral particle from infected cells and are active against flu A and flu B. Amantadine and rimantadine inhibit the protein M2 and viral uncoating. These drugs have important drawbacks including neurological toxicity, they can't be administrated to subjects younger than 12 year-old, finally, they have to be taken at the time of onset of symptoms. Furthermore, they can very frequentely cause the induction of drug-resistant strains. Moreover, although an anti-flu vaccine is available, it has to be changed every year because the virus is prone to antigenic modifications. For all of the above, there is still an urgent need for effective anti-flu compounds with a different mechanism of action from the current anti-flu drugs. A possible novel anti-influenza strategy is rapresented by the RNA polymerase encoded by flu virus; in fact, the influenza virus polymerase is a conserved element among different viral ...